PENGGUNAAN TABUNGAN KEPINGAN SEBAGAI REWARD DALAM MENINGKATKAN KEMAMPUAN MEMBACA KATA BENDA BAGI ANAK BERKESULITAN BELAJAR KELAS D.2 DI SDN 27 OLO PADANG BARAT - Hayatul - Najmi (Jurnal Penelitian Pendidikan Khusus, 2014)
This research was motivated by the problems that researcher shave foundthata child in elementary school SDN 27 class 2 Olo PadangWest. Children have difficulty in recognizing the alphabet at random, read a syll able, word reading and reading correctly and smoothly. This research is anexperimental studyin a single subject reseach(SSR) using AB designsan data analysis techniq uesusing visual analysischart. The subjects werechildren'sreading difficulties. Assesment of this researchis tomeasurethe percentage ofchildren's ability toread words.